Implementasi Budaya Strategis Prancis melalui Prinsip Anti-Terroriste dalam Operasi Serval (2013-2014) - Filasafia Marsya Ma’rifat (Universitas Airlangga, 2021)
Each country has its own Strategic Culture in maintaining its national defenseand security. In French case, its Strategic Culture emphasizes national grandeuror glory. Departing from de Gaulle’s vision in the past, France is a country thatremains actively involved in maintaining global peace and plays role as an intermediary,mediator, and critic within the dynamics of international relations.France also has the principle of “Anti-Terroriste” which sees that terrorism as amajor threat to its national defense and security. It should be noted that Francehas a long history of war on terror, as it had faced in the 1970, 1985, and 1990s.In today’s world, acts of terrorism is even more sophisticated, complex, and globalized.Through Operation Serval in 2013, it could be interpreted as France’sconsistency in combating terrorism in Mali, West Africa. By using the concept ofStrategic Culture and four analysis variables, which is identity, values, norms,and perceptive lens, this paper intends to analyze the basic foundation and directionof France’s Strategic Culture and the accompanying interests.